A surface modifier enhances the performance of the all-inorganic CsPbI2Br perovskite solar cells with efficiencies approaching 15%. Issue 32 (6th August 2020) - Wang, Kaiyuan; Zhou, Jiyu; Li, Xing; Ahmad, Nafees; Xia, Haoran; Wu, Guangbao; Zhang, Xuning; Wang, Boxing; Zhang, Dongyang; Zou, Yu; Zhou, Huiqiong; Zhang, Yuan
Abstract : We propose a surface modification approach based on methyl ammonium halide (MAX) for CsPbI2 Br perovskite solar cells. As a result, trap-assisted recombination is suppressed accompanied by sufficient charge extraction, which boosts the efficiency to 14.8% with an impressive FF of 82.2%. Abstract : All-inorganic perovskite solar cells (PSCs) are attracting considerable attention due to their promising thermal stability, but their inferior power-conversion efficiencies (PCE) hinder their realistic application. Here, we propose an approach through surface modification based on methyl ammonium halide (MAX) for inorganic CsPbI2 Br solar cells processed at a low temperature. The combined benefits of the introduced MAX modifier enable the boosting of the power conversion efficiency to 14.8% with an impressive FF of 82.2% in CsPbI2 Br PSCs. Our experimental analyses coupled with optical modeling indicate that the incorporated MAX leads to an effective passivation of the surface traps originating from Pb 2+ and I − ions in CsPbI2 Br and simultaneously mediates the crystallization of CsPbI2 Br with slightly enlarged grains and reduced numbers of structural defects and pinhole. As a result, the interfacial trap-assisted recombination is suppressed and the charge extraction is promoted. Mechanistically, we show that in the presence of MAX, the deep-level traps in the perovskites are passivated, leaving the energy of the trapping centers to become shallower. In this situation, the negative impacts of the traps on carrier transport and recombination are mitigated.